1964
DOI: 10.1017/s0025315400024711
|View full text |Cite
|
Sign up to set email alerts
|

The Integumentary Mucous Secretions of the Ophiuroid Ophiocomina Nigra

Abstract: The general histology of the integument of the ophiuroid Ophiocomina nigra is outlined. Two types of integumentary mucous glands are described in detail for the first time. The first is a multicellular gland, the basal end of which is located deep within the calcareous layer of the integument. The source of the secretion is a variable number of nuclei embedded in a common cytoplasmic mass filled with fine basiphil granules. These cells contributed their secretion to a duct which pursues a tortuous course throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1969
1969
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 12 publications
(12 reference statements)
1
32
1
Order By: Relevance
“…They avoid encounter with predators by responding to chemical exudates from the predators (Feder & Arvidsson 1967) or injured conspecifics (Rosenberg & Selander 2000) and by hiding in refuges (Hendler 1984, Witman 1985. Once there has been contact with a predator, ophiuroids can avoid being eaten by using active flight (Feder & Arvidsson 1967, Skold 1998, arm autotomy (Wilkie 1978), protective secretions (Fontaine 1964) and bioluminescence (which may function as aposematic coloration; Grober 1988a,b, Deheyn et al 2000. Cryptic ophiuroids may also retreat deeper into refuges to stay out of reach of the predator (Solan & Battle 2003) In the subtidal community of the Mingan Islands in the northern Gulf of St. Lawrence (eastern Canada), the brittle star Ophiopholis aculeata occurs in dense populations (up to 1700 ind.…”
Section: Introductionmentioning
confidence: 99%
“…They avoid encounter with predators by responding to chemical exudates from the predators (Feder & Arvidsson 1967) or injured conspecifics (Rosenberg & Selander 2000) and by hiding in refuges (Hendler 1984, Witman 1985. Once there has been contact with a predator, ophiuroids can avoid being eaten by using active flight (Feder & Arvidsson 1967, Skold 1998, arm autotomy (Wilkie 1978), protective secretions (Fontaine 1964) and bioluminescence (which may function as aposematic coloration; Grober 1988a,b, Deheyn et al 2000. Cryptic ophiuroids may also retreat deeper into refuges to stay out of reach of the predator (Solan & Battle 2003) In the subtidal community of the Mingan Islands in the northern Gulf of St. Lawrence (eastern Canada), the brittle star Ophiopholis aculeata occurs in dense populations (up to 1700 ind.…”
Section: Introductionmentioning
confidence: 99%
“…But he found that, unlike L. ciliaris, L. sarsi does not attack Ophiocomina even when starved. Ophiocomina secretes a mucous layer on the skin which has a repellent effect on predators (Fontaine, 1964). This does not appear to be effective against L. ciliaris (cf.…”
mentioning
confidence: 99%
“…Although it has long been recognized that many ophiuroid spines had a hollow central axis bearing nervous tissue (Buchanan, 1963;Fontaine, 1964), the present work shows, for O. nigra, that this tissue consists of two distinct nerves. Presumably, the spine nerves originate from the segmental nerve that penetrates the lateral arm plate and enters the spine through an aperture located on the articular surface of the spine (Byrne, 1994).…”
Section: Nervous Systemmentioning
confidence: 49%
“…Three types of secretory cells are generally recognized in the ophiuroid epidermis: (1) mucous cells containing an electron-lucent diffuse material packaged in irregular vesicles; (2) granulated cells containing an electron-dense compact material packaged in vesicles; and (3) fibrillar cells containing a moderately electron-dense material organized into parallel strands (Byrne, 1994). The secretory products of these cells are usually composed of mucopolysaccharides and have generally been attributed a feeding or defensive role (Buchanan, 1963;Fontaine, 1964;Pentreath, 1970). Recent work has concentrated on the sensory abilities of the spines ) and close association has been shown between sensory and secretory cells (Whitfield & Emson, 1983).…”
Section: Introductionmentioning
confidence: 99%